Confirmed record of Monodactylus argenteus (Linnaeus, 1758) (Family Monodactylidae) from Jubail, Saudi Arabia, Arabian Gulf - L. A. Jawad (Arxius de Miscel-lània Zoològica)
The first record of M. argenteus from the Arabian Gulf coasts of Saudi Arabia is confirmed, based on a sample measuring 158 mm in SL. Morphometric and meristic data are provided for this specimen.